THE EFFECT OF PROFITABILITY, LEVERAGE AND PUBLIC SHARE OWNERSHIP ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE WITH THE BOARD OF COMMISSIONERS AS A MODERATING VARIABLE IN MINING SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2019–2021 - Novia Riani; Fachrudin; Bambang Satriawan; Chablullah Wibisono; Irfan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to analyze the effect of profitability, leverage and public share ownership on corporate social responsibility disclosure with the board of commissioners as moderating variables in mining companies listed on the IDX in 2019-2021. The population in this study amounted to 31 mining companies. The sample selection method used purposive sampling technique. The type of data used is secondary data with data analysis techniques used, namely panel data regression analysis with multiple linear regression tests using Eviews software. The results show that Profitability has a positive and significant effect on Corporate Social Responsibility Disclosure, Leverage has a negative and significant effect on Corporate Social Responsibility Disclosure,